Synthesis of biodiesel over zirconia-supported isopoly and heteropoly tungstate catalysts - Sunita, G.; Devassy, Biju M.; Vinu, Ajayan; Sawant, Dhanashri P.; Balasubramanian, Veerappan V.; Halligudi, Shivappa B. (Catalysis Communications, 2008)
The liquid-phase synthesis of biodiesel by transesterification of sunflower oil with methanol is carried out by using zirconia-supported isopoly and heteropoly tungstates (HPAs) as catalysts. The isopoly and heteropoly tungstate catalysts were prepared by suspending zirconium oxyhydroxide in water/methanol solution of ammonium metatungstate/silicotungstic acid, phosphotungstic acid (WO3/HPA loading, 15%,,) followed by drying and calcination at 750 degrees C. The catalysts were characterized by XRD, Raman spectroscopy, IR spectroscopy, NH3-TPD and FTIR pyridine adsorption spectroscopy. XRD results indicate that the presence of isopoly and heteropoly tungstates stabilizes ZrO2 in tetragonal phase. Raman and IR spectra of the catalysts show that tungstate species exist as zirconia-anchored octahedral mono-oxotungstate. The acidity measurements by NH3-TPD and FTIR pyridine adsorption spectroscopy show that zirconia-supported phosphotungstate has the highest total acidity and zirconia-supported isopoly tungstate has the highest Bronsted acidity. The zirconia-supported isopoly tungstate shows superior catalytic performance compared to zirconia-supported heteropoly tungstate catalysts. Under the reaction conditions of 200 degrees C and methanol/oil molar ratio 15, 15% WO3/ZrO2 calcined at 750 degrees C gave 97% conversion of oil. This catalyst also efficiently catalyzes methanolysis of other vegetable oils like mustard oil and sesame oil. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; phosphotungstic acids; Silicotungstic acid; transesterification; tungsten oxide; Zirconia